Study of combination of pumpkin seed flour and turkey meat in hams - Galenko, Oleg; Hasyuk, Ostap; Kravchuk, Valentyna; Medianuk, Mariia (My University, 2021)
Introduction. Studies have been conducted to determine the effect of combination of pumpkin seed llour and turkey meat in hams. Materials and methods. The technology of hams with the use of mathematical modulation and addition to the composition of pumpkin seed flour and turkey meat was studies. Determination of amino acid composition was conducted in accordance with the method of ion exchange chromatography Results and discussion. The share of muscle tissue in turkey carcasses of the 1st and 2nd grades is within 44-47% and is dominant, the skin content with subcutaneous fat is 13- 22%. Determined that the protein content of oilseeds is indistinguishable from meat raw materials, and they can be considered as a good source of vegetable protein (19.4- 34.2%). Analysis of the amino acid composition of oilseeds proteins showed that they containe all essential amino acids, but there are minor differences in their quantitative content. In oilseeds, the predominant amino acid is leucine for sesame seeds, leucine and valine for sunflower seeds, phenylaline for pumpkin seeds. Three experimental recipes for restructured ham were developed with the replacement of turkey meat with turkey skin in the amount of 10% and pumpkin seed flour in the amount of 5, 10, 15% hydrated in a ratio of 1:2. Physico-chemical studies have shown that ham made with Ihc use of turkey skin and pumpkin seed flour have slightly higher protein content and more balanced ratio of protein and fal in Ihe recipe 1:1, according to adequate nutrition, Conclusions. The high quality of three formulations developed and Icslcd for the production of restructured ham, in which 10% of turkey skin and 5-15% of pumpkin seed flour are combined, has been established.
Keywords: кафедра технології м’яса і м’ясних продуктів; flour ham; meat; ham; turkey; pumpkin seed